IMPLEMENTATION OF KAHOOT ONLINE AND GOOGLE FORM TOWARD STUDENTS’ VOCABULARY COMPREHENSION ENHANCEMENT - Jenny Elvinna Manurung (Didascein : Journal of English Education, 2021)
Vocabulary is one of the fundamental components learned in language learning. The teachers should prepare good English materials to support the students’ learning activities during vocabulary instruction. Kahoot Online application and Google Form can be used as learning alternative to facilite the process of vocabulary instruction. This study was intended to find out (1) the students’ vocabulary achievement after being treated with Kahoot Online and Google and (2) the significant difference in implementing Kahoot Online Application and Google Form toward students’ vocabulary comprehension enhancement. The researcher used quasi-experimental method to conduct the research. The population of this study were all elementary students of SD Manggala in academic year 2020/2021. All fourth grade students had been involved in this study as the sample. The sample of this study used purposive sampling. The independent sample t-test results showed that the value significance (2-tailed) 0.096 was higher than the value significance 0.05. While, the value of t-obtained (1.319) was lower than t-table (1.6909) with degree of freedom was 34. In other words, there was no any significant difference on vocabulary comprehension between the third grade students of SD Manggala who were taught by using Kahoot Online Application strategy and Google Form (Vocabulary Quiz). Keywords: Kahoot Online Application, Google Form, Vocabulary Comprehension